Kryminalne światy Katarzyny Bondy - o powieściach kryminalnych z cyklu "Cztery żywioły Saszy Załuskiej" = Criminal worlds of Katarzyna Bonda - on crime novels in the series "Cztery żywioły Saszy Załuskiej" - Żmudziak, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Crime novels belong to the fastest developing contemporary literary genre, which break the norms and limitations that have been imposed by its practitioners and theoreticians. The novels have begun to comment explicitly on our reality. The question "Who murdered?", is of a lesser importance. What turns out to be more interesting is the answer to the question: "How and why was the crime committed?".
Keywords: Bonda, Katarzyna (1977- ) - twórczość; powieść kryminalna; literatura polska - 21 w.